The bone attachments of the medial collateral and posterior oblique ligaments are defined anatomically and radiographically - Athwal,KK; Willinger,L; Shinohara,S; Ball,S; Williams,A; Amis,AA (Knee Surgery Sports Traumatology Arthroscopy, 2020)
PurposeTo define the bony attachments of the medial ligaments relative to anatomical and radiographic bony landmarks, providing information for medial collateral ligament (MCL) surgery.MethodThe femoral and tibial attachments of the superficial MCL (sMCL), deep MCL (dMCL) and posterior oblique ligament (POL), plus the medial epicondyle (ME) were defined by radiopaque staples in 22 knees. These were measured radiographically and optically; the precision was calculated and data normalised to the sizes of the condyles. Femoral locations were referenced to the ME and to Blumensaat’s line and the posterior cortex.ResultsThe femoral sMCL attachment enveloped the ME, centred 1 mm proximal to it, at 37 ± 2 mm (normalised at 53 ± 2%) posterior to the most-anterior condyle border. The femoral dMCL attachment was 6 mm (8%) distal and 5 mm (7%) posterior to the ME. The femoral POL attachment was 4 mm (5%) proximal and 11 mm (15%) posterior to the ME. The tibial sMCL attachment spread from 42 to 71 mm (81–137% of A-P plateau width) below the tibial plateau. The dMCL fanned out anterodistally to a wide tibial attachment 8 mm below the plateau and between 17 and 39 mm (33–76%) A-P. The POL attached 5 mm below the plateau, posterior to the dMCL. The 95% CI intra-observer was ± 0.6 mm, inter-observer ± 1.3 mm for digitisation. The inter-observer ICC for radiographs was 0.922.ConclusionThe bone attachments of the medial knee ligaments are located in relation to knee dimensions and osseous landmarks. These data facilitate repairs and reconstructions that can restore physiological laxity and stability patterns across the arc of knee flexion.